Seismic Vulnerability Assessment, Importance of Retrofitting with Measures to Safeguard Schools in India from Natural Calamity like Earthquake - Kharbanda, Siddharth (Journal of Advanced Research in English & Education, 2022)
As per National Disaster Management Authority (NDMA), more than 90% fatalities in past earthquakes in India have occurred due to collapse of houses and structures1. Significant improvements can be done towards reducing loss of life by undertaking seismic strengthening of non-engineered structures. This is the most critical step in earthquake disaster management and mitigation in India. In the Bhuj earthquake of 2001, 971 students and 31 teachers died, 1884 school buildings collapsed, 5950 classrooms destroyed, 11761 school buildings suffered major to minor damages, 36584 rooms declared unfit for holding instruction sessions2. As per NDMA, there were about 19 crore children in the age group of 05 to 14 enrolled in 12 lakh schools in the country in 20043. 229 districts in 22 States & UTs fall in the seismic zones IV & V. There are 241 multi-hazards districts in the country and in all major natural disasters, school buildings have suffered damages, destruction and loss of lives of children. School safety thus becomes one of the most important obligation and objective for the country. How to cite this article: Kharbanda S. Seismic Vulnerability Assessment, Importance of Retrofitting with Measures to Safeguard Schools in India from Natural Calamity like Earthquake. J Adv Res Eng & Edu 2022; 7(4): 10-15